The importance of examining movements within the US health care system: sequential logit modeling - Lee Chioun; Ayers Stephanie L; Kronenfeld Jennie; Frimpong Jemima A; Rivers Patrick A; Kim Sam S (BMC, 2010)
Abstract Background Utilization of specialty care may not be a discrete, isolated behavior but rather, a behavior of sequential movements within the health care system. Although patients may often visit their primary care physician and receive a referral before utilizing specialty care, prior studies have underestimated the importance of accounting for these sequential movements. Methods The sample included 6,772 adults aged 18 years and older who participated in the 2001 Survey on Disparities in Quality of Care, sponsored by the Commonwealth Fund. A sequential logit model was used to account for movement in all stages of utilization: use of any health services (i.e., first stage), having a perceived need for specialty care (i.e., second stage), and utilization of specialty care (i.e., third stage). In the sequential logit model, all stages are nested within the previous stage. Results Gender, race/ethnicity, education and poor health had significant explanatory effects with regard to use of any health services and having a perceived need for specialty care, however racial/ethnic, gender, and educational disparities were not present in utilization of specialty care. After controlling for use of any health services and having a perceived need for specialty care, inability to pay for specialty care via income (AOR = 1.334, CI = 1.10 to 1.62) or health insurance (unstable insurance: AOR = 0.26, CI = 0.14 to 0.48; no insurance: AOR = 0.12, CI = 0.07 to 0.20) were significant barriers to utilization of specialty care. Conclusions Use of a sequential logit model to examine utilization of specialty care resulted in a detailed representation of utilization behaviors and patient characteristics that impact these behaviors at all stages within the health care system. After controlling for sequential movements within the health care system, the biggest barrier to utilizing specialty care is the inability to pay, while racial, gender, and educational disparities diminish to non-significance. Findings from this study represent how Americans use the health care system and more precisely reveals the disparities and inequalities in the U.S. health care system.